Employee Performance Evaluation of Village-Owned Enterprises (Bumdes) in Sukaraharja Village, Kadupandak District, Cianjur Regency - Andi Saputra; Samsul Ode (Department of Public Administration, 2023)
This study aims to evaluate the performance of village-owned enterprises (BUMDes) employees in Sukaraharja Village, Kadupandak District, Cianjur Regency. BUMDes is an economic institution owned and managed by village communities to increase village potential and reduce poverty. However, there are still problems related to human resources (HR) in BUMDes management, such as the limited number of employees and the lack of focus on BUMDes by management. This study uses a qualitative approach to evaluate the performance of BUMDes employees in Sukaraharja Village. Data were obtained through direct observation and interviews with BUMDes employees and analysis of related documents. The qualitative approach was chosen because of the complexity of the research subject. The results showed that the performance of BUMDes employees in Sukaraharja Village affected the operational efficiency of BUMDes and their productivity. Skilled, trained and professional employees can optimize BUMDes business processes, produce more in less time, and provide good service to the community. However, researchers also found that there were employees who lacked the necessary professionalism and competence. In the context of improving the performance of BUMDes employees, factors such as education, work experience, compensation, work environment, leadership style, and motivation have a significant influence. Good education and work experience improve employee abilities and skills, while adequate compensation encourages better performance. A good work environment, appropriate leadership style, and high motivation also contribute to improving employee performance. Based on these findings, the researcher recommends the need for periodic evaluation of the performance of BUMDes employees. This evaluation can help identify employee strengths and weaknesses, as well as provide a basis for developing training programs and improving performance. In addition, it is also important to improve the facilities and infrastructure that support BUMDes operations and to optimize BUMDes product marketing efforts to the public